Pemberdayaan Masyarakat Berbasis Masjid dan Gereja Studi Kasus Aceh Barat dan Tana Toraja - Hendismi, Hendismi; Al Fairusy, Muhajir; Ramli, Ramli (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2024)
This study aims to explore the role of mosques and churches in community empowerment in Aceh and Tana Toraja. Focus of this research is to understand how the empowerment programs initiated by Baitil Abrar Mosque in Aceh and Toraja Church Jemaat Padakka in Tana Toraja can enhance the social and economic welfare of the local community. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis. Data analysis was conducted thematically to identify the main patterns emerging from the field data. The research findings indicate that the empowerment programs initiated by Baitil Abrar Mosque and Toraja Church Jemaat Padakka have successfully improved the social and economic welfare of the community. These programs include education, skills training, economic development, and the empowerment of women and children. An increase in income and economic independence of the local community is one of the positive impacts of these programs. Additionally, there is an improvement in the quality of education and skills, as well as awareness of gender equality and children's rights. This study suggests that cooperation among various parties should be strengthened and that empowerment programs should continue to be developed with a participatory and sustainable approach.